Economic Devastation: The Impact of the Israeli War on Gaza’s Work and Economic Growth - Migdad, Mohammed; Migdad, Abdalrahman; Migdad, Isra; Hassoun, Abdo; Mıgdad, Abdalrahman M.I. (Springer Nature, 2025)
This chapter examines the severe economic consequences of the recent war on Gaza, focusing on Sustainable Development Goal 8 (SDG 8), which aims to achieve inclusive economic growth and decent work for all. This genocidal war has caused extensive job losses, destruction of industries, and widespread poverty, while the devastation of infrastructure has undermined economic stability. Movement restrictions, the blockade, and military operations have disrupted trade and humanitarian aid, further worsening economic conditions. Unemployment has surged, particularly among youth and women, while unsafe working conditions and the rise in child labor reflect dire socioeconomic conditions. The destruction of businesses, along with educational and vocational facilities, has severely hindered skill development and undermined long-term economic prospects. However, amidst the devastation, inspiring examples of resilience and innovation, such as youth-led entrepreneurial ventures and community-driven initiatives, demonstrate the potential for recovery and economic renewal. This chapter highlights the urgent need for sustainable peace and international interventions to rebuild Gaza’s economy. Strategies for recovery, including infrastructure reconstruction, job creation, and fostering local entrepreneurship, are explored, underscoring the importance of restoring economic stability and achieving the inclusive and sustainable development envisioned by SDG 8.